2009
DOI: 10.5194/acp-9-3223-2009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of mineral dust altering cloud microphysics and precipitation

Abstract: Abstract. Multi-platform and multi-sensor observations are employed to investigate the impact of mineral dust on cloud microphysical and precipitation processes in mesoscale convective systems. For a given convective strength, small hydrometeors were more prevalent in the stratiform rain regions with dust than in those regions that were dust free. Evidence of abundant cloud ice particles in the dust sector, particularly at altitudes where heterogeneous nucleation of mineral dust prevails, further supports the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 26 publications
8
93
2
Order By: Relevance
“…Their results were in agreement with past studies focusing on the Sahel that showed similar correlation between rainfall anomalies and dust occurrence (Mbourou et al, 1997). Min et al (2009) used integrated data from a few remote sensing instruments that measured cloud and aerosol properties in a trans-Atlantic dust outbreak of Saharan origin and found that precipitation had been reduced in areas where dust was present.…”
supporting
confidence: 79%
“…Their results were in agreement with past studies focusing on the Sahel that showed similar correlation between rainfall anomalies and dust occurrence (Mbourou et al, 1997). Min et al (2009) used integrated data from a few remote sensing instruments that measured cloud and aerosol properties in a trans-Atlantic dust outbreak of Saharan origin and found that precipitation had been reduced in areas where dust was present.…”
supporting
confidence: 79%
“…In the regime of temperatures warmer than −36 • C, even small fractions (<1%) of dust able to initiate the ice phase will be important for the shift from liquid to mixed-phase clouds and for impacting precipitation processes, depending on dust number concentrations. Min et al (2009) used observations of a mesoscale convective system that was partially influenced by elevated dust concentrations and found large increases in ice crystal concentration, yielding smaller crystals and suppressing precipitation. It should also be noted that in this study we could not measure the role of contact freezing nucleation, which could be efficient under warmer temperature conditions.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…For example, vapor can deposit as ice directly on an aerosol surface by deposition nucleation or aerosols can take up water and activate to liquid droplets with the insoluble material subsequently initiating freezing through condensation or immersion freezing. Recent studies have suggested that dust from arid regions can influence the microphysics of warm and cold cloud formation worldwide DeMott et al, 2003b;Sassen, 2002;Mahowald and Kiehl, 2003;Stith et al, 2009;Min et al, 2009). Laboratory studies confirm the ability of Saharan dust to nucleate ice at relative humidities with respect to water that are up to 20% lower than those required for homogeneous freezing of background sulfate aerosols at low temperatures Kanji and Abbatt, 2006); these studies also demonstrate heterogeneous ice nucleation ability to temperatures at least as warm as −20 • C. DeMott et al (2003b) measured ice nuclei (IN) concentrations up to 0.3 cm −3 , at 86% relative humidity with respect to water (RH w ) at −36 • C, an observation that is only explicable by the presence of highly efficient IN in the Saharan dust plumes sampled near Florida.…”
Section: Introductionmentioning
confidence: 99%
“…Alpert et al (1998) discussed the response of the atmospheric temperature field to the radiative forcing of Saharan dust over the North Atlantic Ocean. Dust particles over the Atlantic Ocean may essentially influence tropical cloud systems and precipitation (Kaufman, Koren, et al 2005;Johnson, Shine, and Forster 2004;Min et al 2009;BenAmi, Koren, and Altaratz 2009;Feingold et al 2009;Rosenfeld, Rudich, and Lahav 2001).…”
Section: Introductionmentioning
confidence: 99%